ANALISIS JENIS-JENIS BULLYING DAN KONDISI PSIKOLOGIS BAGI SISWA SMA NEGERI 12 PEKANBARU - Syahputra, Angga Dwi; Saam, Zulfan; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Bullying is a negative action which is conducted to other people either physically or verbally repeatedly and causes other people to feel disturbed, uncomfortable, even feel tortured. Bullying is caused by several trigger factors, such as: religion, physical condition, family, economy, and gender. Bullying that is carried out will create a discriminatory (disharmonious) environment so that the victim will feel pressured. Bullying behavior can affect the psychological condition of the victim so that the victim will experience depression, lack of self-confidence, social isolation and even thoughts of suicide. Bullying can happen anywhere, including in educational institutions. This study aims to determine the types of bullying behavior and psychological conditions in SMA Negeri 12 Pekanbaru. The method used in this study is a quantitative method with a descriptive approach to determine the types of bullying, the level of bullying behavior, and the psychological condition of victims of bullying at SMA Negeri 12 Pekanbaru. Subjects in this study amounted to 30 people who analyzed the level of bullying behavior received and its psychological condition. The data collection technique used is purposive sampling. Data was collected using a questionnaire instrument for victims of bullying as many as 28 items and the psychological condition of victims of bullying as many as 21 items. Based on the result gained from this study, it was found that not many respondents were victims of bullying at the school. However, there are still some bullying behaviors that occur both physically and verbally. The form of physical bullying such as, hitting, forcing, disturbing, and damaging things. While the forms of verbal bullying experienced by students in the form of being yelled at, insulted and given nicknames such as